1969
DOI: 10.1177/001979396902200202
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Reinstatement as a Public Policy Remedy: The Kohler Case

Abstract: This article is concerned with two aspects of the NLRB reinstatement remedy as applied in the famous Kohler case: (1) how effective the remedy was, particularly in terms of the number of employees who returned to Kohler under its protection, and (2) what factors, in order of significance, affected a worker's decision to return. The authors find the remedy was effective, since about 40 percent of those workers who received reinstatement offers accepted them. Regression and discriminant analyses of the variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Much attention has been devoted by industrial relations and legal scholars to the effectiveness of NLRB remedies for violations of the Act (Bok 1964;Bredhoff 1974;Drotning and Lipsky 1969;Farber 1954;Greer and Martin 1978;Gross, Cullen, and Hanslowe 1968;Hood 1981;King 1977;Kleiner and Schliebs, forthcoming;Kramer 1967;McCulloch 1968;Murphy 1981;Nolan and Lehr 1979;O'Hara and Pollitt 1968;Peck 1961;Roomkin 1981;Ross 1966;St. Antoine 1968a;Samoff 1965;Smisek 1983;University of Chicago Law Review 1968;Wall 1982;Wolkinson 1969).…”
Section: Section 8: Workers' Protectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Much attention has been devoted by industrial relations and legal scholars to the effectiveness of NLRB remedies for violations of the Act (Bok 1964;Bredhoff 1974;Drotning and Lipsky 1969;Farber 1954;Greer and Martin 1978;Gross, Cullen, and Hanslowe 1968;Hood 1981;King 1977;Kleiner and Schliebs, forthcoming;Kramer 1967;McCulloch 1968;Murphy 1981;Nolan and Lehr 1979;O'Hara and Pollitt 1968;Peck 1961;Roomkin 1981;Ross 1966;St. Antoine 1968a;Samoff 1965;Smisek 1983;University of Chicago Law Review 1968;Wall 1982;Wolkinson 1969).…”
Section: Section 8: Workers' Protectionsmentioning
confidence: 99%
“…First, workers suffering illegal discrimination normally wait a long time for little or no relief (see the case incidents reported in O'Hara and Pollitt, 1968, andin Samnoff, 1965). For all ?8 charges, it has been reported that in 1980 it took a median of 484 days to obtain an NLRB decision after complaint filing and an additional 485 days to obtain a court of appeals decision (Weiler 1983(Weiler : 1795; some ULP charges have taken four, six, or even ten years to be resolved (O'Hara and Pollitt 1968;Drotning and Lipsky 1969). If "justice delayed is justice denied," then the Act's adminis-'2But some scholars have concluded that NLRB remedies are effective in some circumstances (see Drotning and Lipsky 1969;Wolkinson 1969).…”
Section: Section 8: Workers' Protectionsmentioning
confidence: 99%
See 2 more Smart Citations